Junior High School Science Teachers’ Perception Of Their Technological Pedgogical Content Knowledge (Tpack) - Baah Joseph Kobina (University of Cape Coast, 2024)
The purpose of this study was to examine science teachers' perception of their technological pedagogical content knowledge (TPACK) in Central region of Ghana. The specific objective of the study was to examine the perceived understanding of Junior High School (JHS) science teachers in the various constructs of TPACK framework. The study also looked at the extent to which content knowledge (CK), pedagogical knowledge (PK), technological knowledge (TK), pedagogical content knowledge (PCK), technological content knowledge (TCK) and technological pedagogical knowledge (TPK) correlate with TPACK (also referred to as TPCK). The study finally identified the influence of gender and teaching experience of science teachers’ TPACK. The study used cross sectional survey design. The study used questionnaire to gather primary data to address the research questions. The study used proportionate sampling to select a sample size of 155 JHS science teachers. Results were analysed using frequency, Mean and standard deviation and simple linear multiple regression. Based on the results of this study it was concluded that Komenda Edina Equafo Abream (KEEA) municipality and Cape Coast metropolis JHS teachers who teach integrated science have high-perceived understanding of TPACK constructs. TPCK has highly positive correlation with the other six constructs. From the results, it can be concluded that JHS integrated science teachers in these two municipalities have high-perceived understanding of TPACK framework constructs.
xiii,174p:,ill
Keywords: Content Knowledge Educational Technology Pedagogical Knowledge Technological Knowledge Technological Integration Technological Content Knowledge Technological Pedagogical Knowledge